(untitled) (Technological Innovations Journal, 2022)
The purpose of this research was to identify through a Systematic Review (SR) the relationship between Emotional Intelligence (EI) and the use of Information and Communication Technologies (ICT) on student motivation and academic performance. For this purpose, two searches were carried out in scientific electronic resources, such as Web of Science, Scopus, PubMed, PsycINFO and Dialnet. In this way, a total of 98 studies were obtained which, after applying the inclusion and exclusion criteria, left a total of 39 papers for review. The results show that EI and the use of ICTs have a positive relationship on motivation and academic performance. The most relevant conclusions suggest that the level of EI favors personal well-being, the improvement of school coexistence and the correct use of ICT. Likewise, the use of digital resources in the educational context increases motivation, academic performance and the achievement of curricular objectives in the different educational stages. However, it is suggested that further research should be carried out to confirm the findings of this paper.